Atypical Cutaneous Fibrous Histiocytoma: An Unusual and Misleading Variant of Fibrous Histiocytoma - Soumaya Ben Abdelkrim; Colondane Belajouza; Wafa Jomaa; Nadia Beizig; Zeineb Ben Said; Moncef Mokni; Rafia Nouira; Badreddine Sriha (Hindawi Limited, 2011)
Atypical fibrous histiocytoma is a distinctive variant of cutaneous fibrous histiocytoma, which is often mistaken histologically for sarcoma and which have a tendency to recur locally and a capacity to metastasize, although very rarely. We report a new case of atypical cutaneous fibrous histiocytoma in a 31-year-old man who presented with a recurrent polypoid nodule on the abdominal wall. The diagnosis was made on the basis of morphological and immunohistochemical findings. We discuss through this case and a review of the literature pathological and evolutive features and diagnostic difficulties of this entity.